A-Fe2O3modified TiO2nanoparticulate films prepared by sparking off Fe electroplated Ti tips - A. Hankhuntod (2018)
© 2017. α-Fe 2 O 3 modified TiO 2 nanoparticulate (NP) films were successfully prepared by sparking off Fe-coated Ti wires using an electroplating technique. An aqueous iron (III) nitrate with the concentration of 0.01 M was used as the electrolyte. The experiment was carried out using a 0.1 μA of DC current applied to Ti wires which were dipped in the electrolyte for 15-135 s. The NP films were then formed by sparking the Fe-coated Ti wires using a high DC voltage of 3.0 kV and a limited current of 3 mA. The as-deposited NP films with high porosity were annealed at 250 and 500 °C under atmospheric pressure for 1 h. The films were then characterized in terms of morphology as well as structural and optical properties using SEM, Raman spectroscopy and UV/vis spectroscopy, respectively. Electroplating Ti wires with an Fe coating for increasing lengths of time had the effect of increasing the tip diameter and thickness from 252.5 to 259.2 μm and 0-3.3 μm, respectively. Raman spectra showed that the annealed films at 500 °C were composed of the anatase TiO 2 phase at 145 cm -1 and the hematite Fe 2 O 3 phase at 222, 289, 406 and 612 cm -1 . The energy band gap of the annealed films at 500 °C, calculated using the transmission spectra, decreased from 3.27 to 2.95 as the electroplating time increased from 0 to 135 s. Finally, it was observed that the NP film electroplated for 135 s showed the highest degradation of methylene blue (MB) at 662 nm when exposed to visible light for 1 h. This result represents a 37% enhancement in the visible-light photocatalytic activity.